Revision of the genus Glyphotmethis Bey-Bienko, 1951 (Orthoptera: Pamphagidae) - Ünal, Mustafa (Zootaxa, 2007)
The complicated genus Glyphotmethis Bey-Bienko, 1951 is revised using the previous materials including the type specimens preserved in Museums and an abundance of new material collected mainly in Turkey. Diagnoses, ecology, distribution and taxonomic characters for the genus are provided. The function of Krauss’ organ is discussed. The followingseven taxa are proposed as junior synonyms: Glyphotmethis holtzi spinosus Karabağ, 1956 is synonym with G. holtzi pulchripes (Uvarov, 1943), Glyphotmethis holtzi extimus Bey-Bienko, 1951 is synonym with G. holtzi holtzi (Werner, 1901), Glyphotmethis escherichi coloripes Cejchan, 1965 is synonym with G. escherichi elatior (Ramme, 1951), Glyphotmethis guichardi Cejchn, 1964 is synonym with G. escherichi escherichi (Krauss, 1896), Glyphotmethis raggei Cejchan, 1965 and Glyphotmethis adaliae angorensis Cejchan, 1965 are synonyms with G. escherichi inermis (Uvarov, 1934) and Glyphotmethis heldreichi macedonicus, Bey-Bienko, 1951 is synonym with G. heldreichi heldreichi (Brunner, 1882). One species, Glyphotmethis arasi, is removed from the genus and three new taxa, Glyphotmethis holtzi brachypterus ssp.n., Glyphotmethis holtzi turcicus ssp.n. and Glyphotmethis efe sp.n. are described. The taxonomical status of some taxa are rearranged. A neotype is designated for Glyphotmethis eshcerichi escherichi (Krauss, 1896) from Ankara known as the type locality. Misidentified specimens and inaccurate records for taxa in previous papers are corrected and their geographical distributions adjusted. Many records are provided for new localities. Keys for the identification of species and subspecies are prepared using traditional and some new distinctive characters. A short description and comparison with close allies are given for each taxon. Distribution areas of the taxa and the contact zones between some subspecies are determined. In addition, 126 figures and 3 distributional maps are given.